Fibrocytes boost tumor-supportive phenotypic switches in the lung cancer niche via the endothelin system - Weigert, Andreas; Zheng, Xiang; Nenzel, Alina; Turkowski, Kati; Günther, Stefan; Strack, Elisabeth; Sirait-Fischer, Evelyn; Elwakeel, Eiman; Kur, Ivan M.; Nikam, Vandana S.; Valasarajan, Chanil; Winter, Hauke; et al. (Nature Communications, 2022)
Fibrocytes are bone marrow-derived monocytic cells implicated in wound healing. Here, we identify their role in lung cancer progression/ metastasis. Selective manipulation of fibrocytes in mouse lung tumor models documents the central role of fibrocytes in boosting niche features and enhancing metastasis. Importantly, lung cancer patients show increased number of circulating fibrocytes and marked fibrocyte accumulation in the cancer niche. Using double and triple co-culture systems with human lung cancer cells, fibrocytes, macrophages and endothelial cells, we substantiate the central features of cancer-supporting niche: enhanced cancer cell proliferation and migration, macrophage activation, augmented endothelial cell sprouting and fibrocyte maturation. Upregulation of endothelin and its receptors are noted, and dual endothelin receptor blockade suppresses all cancer-supportive phenotypic alterations via acting on fibrocyte interaction with the cancer niche. We thus provide evidence for a crucial role of fibrocytes in lung cancer progression and metastasis, suggesting targets for treatment strategies.
Gesehen am 15.12.2022